KUALITAS APARATUR SIPIL NEGARA MELALUI DIKLAT PADA KANTOR SEKRETARIAT DAERAH KABUPATEN MAMUJU - Rustan IR. (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to determine the development of the quality of the state civil apparatus after following the process of education and training carried out by the Regional Secretariat of Mamuju Regency. This research is a type of descriptive qualitative research that provides an explanation of the implementation of education and training to its effect on improving the quality of the State civil apparatus. The results showed that the participation of employees in education and training at the Office of the Regional Education and Training Personnel Agency of Mamuju Regency was still very limited. The number of participants for three years did not meet the needs. The learning system that is applied is less effective in supporting the implementation of tasks and work for participants.